Assessing the quality of life in age-related macular degeneration patients: a cross-sectional study in Kazakhstan: Quality of Life in AMD Patients - Ismayilova, Inara; Turdaliyeva, Botagoz; Aldasheva, Neilya; Veselovskaya, Natalia (Acta Biomedica Atenei Parmensis, 2022)
Aim: The goal of this study was to assess Vision-Related Quality of Life (VRQoL) in patients with Age-Related Macular Degeneration (AMD) and identify its significant predictors. Methods: 458 AMD patients from four eye clinics in three major cities of Kazakhstan were recruited for this study. Data were collected using a structured questionnaire on sociodemographic and visual information and the National Eye Institute-Visual Function Questionnaire-39 (NEI-VFQ-39). Results: The study sample included 181 male patients who were 64.9 years on average (SD±8.4), and 277 female patients who were 68.7 years on average (SD±10.7). The majority of patients had stage 2 (43.7%) or stage 3 (40.2%) AMD according to the Age-Related Eye Disease Study (AREDS) classification. The mean (SD) NEI-VFQ-39 total score was 58.0 (23.8), range (9.8 - 100). The multiple linear regression model showed that the VRQoL of AMD patients correlated with the AMD stage according to the AREDS classification, age of the patients, visual acuity, number of years since the AMD diagnosis, and the city of residence. Conclusions: AMD causes severe vision impairment and daily functioning problems, reducing the quality of life of patients. To diagnose and treat degenerative eye disorders at an early stage, it is essential to inform patients about regular ophthalmological checkups to diagnose and treat degenerative eye disorders at an early stage.